2019
DOI: 10.1101/672428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wide distribution of phage that infect freshwater SAR11 bacteria

Abstract: Fonsibacter (LD12 subclade) are among the most abundant bacterioplankton in freshwater ecosystems. These bacteria belong to the order Pelagibacterales (SAR11) and are related to Pelagibacter (marine SAR11) that dominate many marine habitats. Although a handful of Pelagibacter phage (Pelagiphage) have been described, no phage that infect Fonsibacter have been reported. In this study, a complete Fonsibacter genome containing a prophage was reconstructed from metagenomic data. A circularized and complete genome r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…One possibility is as an effective defense mechanism against abundant viruses. Viruses infecting SAR11 have been shown to be extremely abundant in both marine (115, 116) and freshwater (117) systems. Indeed, the paradox of high viral abundances and high host abundances in SAR11 has led to a refining of negative density dependent selection through Lokta-Volterra predator-prey dynamics (118) to include heterogeneous susceptibility at the strain level (119, 120) and positive density dependent selection through intraspecific proliferation of defense mechanisms (121).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is as an effective defense mechanism against abundant viruses. Viruses infecting SAR11 have been shown to be extremely abundant in both marine (115, 116) and freshwater (117) systems. Indeed, the paradox of high viral abundances and high host abundances in SAR11 has led to a refining of negative density dependent selection through Lokta-Volterra predator-prey dynamics (118) to include heterogeneous susceptibility at the strain level (119, 120) and positive density dependent selection through intraspecific proliferation of defense mechanisms (121).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR and digital droplet PCR techniques have been employed to investigate the absolute abundance of the isolate HTVC010P, which have revealed that the abundance of HTVC010P was within the range of 10 3 -10 4 virus ml −1 in various oceanic regions [27,28]. To date, only two HTVC010P-type isolates [12,16], HTVC010P-type SAR11 prophage PNP1 [20], one HTVC010P-related contig from Western English Channel viral metagenome [29] and three reconstructed HTVC010Prelated freshwater SAR11 phages (fonsiphages) [30] have been reported, limiting our understanding of this important phage group. Therefore, more HTVC010P-type pelagiphages need to be analysed to better understand their diversity and ecology.…”
Section: Open Accessmentioning
confidence: 99%
“…4 ). Recent evidence of prophages in freshwater SAR11 41 and other temperate phages in marine SAR11 42 point to a mechanism capable of mediating significant horizontal gene transfer in the environment.…”
mentioning
confidence: 99%